Breast Implant–Related Outcomes After Cardiothoracic Surgeries and Electrophysiologic Procedures. Issue 3 (28th September 2022) - Coombs, Demetrius M.; Wu, Shannon S.; Bernard, Steven; Djohan, Risal; Isakov, Raymond; Schwarz, Graham; Bassiri Gharb, Bahar; Rampazzo, Antonio
Abstract : Background: Outcomes related to preexisting breast implants after cardiothoracic procedures are poorly characterized. This study evaluated complications after minimally invasive cardiac surgery (MICS), median sternotomy (MS), and electrophysiologic procedures (EP) in patients with preexisting breast implants. Methods: A retrospective review of patients with prior breast implants who underwent MICS, MS, or EP from 1994 to 2019 was performed. Demographic, treatment, and outcome characteristics were recorded. χ 2 Test and analysis of variance were used to perform statistical comparisons. Results: In total, 78 patients (37 MICS, 21 MS, and 20 EP) were identified. Mean breast implant age was 13.3, 11.7, and 10.2 years, respectively ( P = 0.235). Intraoperative plastic surgeon involvement was present in 26 (70.3%) MICS cases, compared with 2 (9.5%) MS and 0% EP ( P < 0.001). Intraoperative rupture occurred in 5 (13.5%) MICS cases and no MS or EP cases ( P < 0.001). Postoperative implant complications occurred in 6 (16.2%) MICS, 8 (38.1%) MS, and 5 (25.0%) EP ( P = 0.350) cases, with median time to complication of 5.9, 5.4, and 38.9 months, respectively ( P = 0.596). Revision surgery was performed in 5 (13.5%) MICS, 7 (33.3%) MS, and 5 (25.0%) EP ( P = 0.246) cases. On multivariate analysis, lack of intraoperative plastic surgeon involvement ( P = 0.034) and breast implant age ( P = 0.001) were significant predictors of postoperative complications. Conclusions: Long-term complication rates are highest among patients with breast implants undergoing MS. Plastic surgeon involvement was significantly associated with fewer postoperative complications. Our results support a multidisciplinary approach to managing breast implants during cardiothoracic procedures.